OBSERVAÇÃO DO DESENVOLVIMENTO DE CRIANÇAS DE ZERO A DOIS ANOS EM ESCOLAS DE EDUCAÇÃO INFANTIL - Freire, Kenia S.; Rossi, Vanessa; Lourega, Ana C. G.; Dias, Luana A. F.; Zambon, Aline B.; Ávila, Cassiana A.; Braganholo, Dalila P.; Wolff, Marcella; Borelli, Paula C. M. (Salão do Conhecimento, 2013)
Resumo